2019
DOI: 10.21660/2019.60.8169
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Method for Long-Term Settlement of Higly Organic Soft Soil

Abstract: One of the prediction method of the long-term settlement of soft clay is to predict it by defining the linear slope of the latter half of the s-log t curve, as the rate of secondary consolidation. This method has some disadvantages, because the slope of the straight line is depending on how to set the origin of elapsed logarithmic time, and how to determine the initial thickness of soil layer, and so on. The author carried out a series of laboratory experiments using oedometer apparatus against some kinds of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Based on existing research, the current methods for predicting ground settlement mainly include purely theoretical calculation methods based on soil consolidation principles [17][18][19], various curvefitting methods based on measured settlement data commonly used in engineering [20][21], and emerging dynamic prediction methods represented by artificial neural network analysis [22][23][24]. In the process of settlement prediction, purely theoretical calculation methods based on ground consolidation settlement principles are overly complex and involve numerous parameters, making them less convenient to use.…”
Section: Introductionmentioning
confidence: 99%
“…Based on existing research, the current methods for predicting ground settlement mainly include purely theoretical calculation methods based on soil consolidation principles [17][18][19], various curvefitting methods based on measured settlement data commonly used in engineering [20][21], and emerging dynamic prediction methods represented by artificial neural network analysis [22][23][24]. In the process of settlement prediction, purely theoretical calculation methods based on ground consolidation settlement principles are overly complex and involve numerous parameters, making them less convenient to use.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou and Shoji analyzed the change in settlement of the soft foundation of an expressway under surcharge unloading and reloading. It was observed that the settlement occurred mostly during the period of filling and surcharge preloading, and the rate of settlement decreased during reloading after surcharge unloading, but it was not accomplished quickly after the reloading period [5,6]. Yang and LI presented a settlement rate method for determining surcharge removal time for an embankment on soft ground.…”
Section: Introductionmentioning
confidence: 99%